PERAN DUKUNGAN KELUARGA, KREATIVITAS, MOTIVASI INTERNAL DALAM MENINGKATKAN KEBERHASILAN USAHA - Marli'aini, Navika Tiamy; Sutianingsih, Sutianingsih (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2023)
This research analyzes the role of family support, creativity, and internal motivation in increasing business success for women entrepreneurs in Surakarta City. Respondents were 100 women entrepreneurs in Surakarta City from various types of businesses. The instrument uses a questionnaire. Data analysis with multiple regression. Research results: family support, creativity, and internal motivation significantly increase business success. Family support has a dominant influence in increasing business success for women entrepreneurs in Surakarta City. Keywords: business success; creativity; family support; internal motivation